An Analysis of the Factors Impacting Satisfaction and Continued Intention to Use Digital Library: A Case Study of Universities in Chongqing, China - Yang, Chengjie (Scholar: Human Sciences, 2024)
Purpose: This study explores the influencing factors of students’ satisfaction and to continued intention to use digital libraries in Chongqing. This study proposes a causal relationship between system quality, perceived ease of use, usefulness, confirmation, information quality, satisfaction, and continued intention. Research design, data, and methods: This study used a quantitative method (n=500) to conduct a questionnaire survey among postgraduates from several universities in Chongqing. The researchers used judgmental, quota, and convenience sampling to collect data in the study. In order to ensure the reliability and reliability, Item-Objective Congruence (IOC), and Cronbach's Alpha method were adopted. Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) were used for data analysis, including model fitting, reliability, and validity. Results: The findings reveal that system quality, perceived ease of use, and information quality exert a substantial influence on satisfaction. Moreover, satisfaction plays a significant role in determining continued intention. However, it's noteworthy that neither usefulness nor confirmation exhibits a significant impact on satisfaction. Conclusion: The research shows that universities should continuously improve the quality of digital library services, systems, and resources, improve the management level, serve the training of postgraduates, and enhance students' satisfaction and continuous use intention.